Exploration of discourse markers in Palembang Malay: Discourse analysis based on Fraser’s theory - Sari, Ayu Puspita Indah; Oberto, Rachel; Mayrita, Hastari; Siahaan, Theodorus William; Ramdhani, Muhammad Iqbal; Amalia, Shynta (Edelweiss Applied Science and Technology, 2024)
Published research on Palembang Malay has been conducted at the phonetic, phonological, morphemic, syntactic, and semantic level, but there is not yet any research available at the discourse or pragmatics level. This research is offered as an initial step in the linguistic discourse analysis of Palembang Malay by applying Fraser’s theory of discourse markers to a recording of oral conversational discourse. The research method used was qualitative descriptive. The data was gathered by recording and transcribing a conversation between two native speakers. The results of this transcription were examined for discourse markers meeting the requirements of Fraser’s theory. The functional class of each marker was then identified as contrastive, elaborative, or inferential. The contrast discourse markers identified were tapi ‘but’ and sebenernyo ‘the truth is’. The elaborative discourse markers identified were suda tu ‘besides that’, suda tu jugo ‘besides that also’, umpamo ‘like’, and mala(han) ‘moreover’. The inferential discourse markers identified were jadi ‘so’, mangkonyo ‘therefore’, and laju ‘so then’. If Fraser’s theory is extended slightly to allow for self-interruption structural sequences, an additional elaborative discourse marker, contonyo ‘for example’, can be identified as well.